A Four‐Step Enzymatic Cascade for Efficient Production of L‐Phenylglycine from Biobased L‐Phenylalanine. (26th February 2022) - Zhu, Yuling; Yuan, Jifeng
Abstract: Enantiopure amino acids are of particular interest in the agrochemical and pharmaceutical industries. Here, we report a multi‐enzyme cascade for efficient production of L‐phenylglycine (L‐Phg) from biobased L‐phenylalanine (L‐Phe). We first attempted to engineer Escherichia coli for expressing L‐amino acid deaminase (LAAD) from Proteus mirabilis, hydroxymandelate synthase (HmaS) from Amycolatopsis orientalis, ( S )‐mandelate dehydrogenase (SMDH) from Pseudomonas putida, the endogenous aminotransferase (AT) encoded by ilvE and L‐glutamate dehydrogenase (GluDH) from E. coli . However, 10 mM L‐Phe only afforded the synthesis of 7.21±0.15 mM L‐Phg. The accumulation of benzoylformic acid suggested that the transamination step might be rate‐limiting. We next used leucine dehydrogenase (LeuDH) from Bacillus cereus to bypass the use of L‐glutamate as amine donor, and 40 mM L‐Phe gave 39.97±3.84 mM (6.04±0.58 g/L) L‐Phg, reaching 99.9 % conversion. In summary, this work demonstrates a concise four‐step enzymatic cascade for L‐Phg synthesis from biobased L‐Phe, with a potential for future industrial applications. Abstract : A concise four‐step enzymatic cascade for L‐phenylglycine synthesis from biobased L‐phenylalanine was devised. Forty millimolar L‐phenylalanine afforded the synthesis of 39.97±3.84 mM (6.04±0.58 g/L) L‐phenylglycine, reaching 99.9 % conversion.